Analysis of the performance of access and quality of the public safety center (PSC) 119 on patient satisfaction at the North Tapanuli District Health Office - Angki, Pebri (Institute of Computer Science (IOCS), 2025)
Public Safety Center (PSC) 119 is an integrated emergency service based on a call center. Patient satisfaction in health services is very important to note because it can describe the quality of service at a health service location. The purpose of this study was to analyze the Influence, Performance, service quality, and access to patient satisfaction of the Public Safety Center (PSC) 119 of the North Tapanuli Health Office in 2024. This research method is descriptive analytic with a correlational design. A total of 150 patients who had used the PSC 119 service at 5 Health Centers in the North Tapanuli Health Office became respondents in this study and were selected using a simple random sampling technique. The research instrument used a questionnaire sheet. Data analysis included univariate analysis, bivariate analysis and multivariate analysis using multiple logistic regression tests. The results of this study indicate that using the Pearson Correlation test and found a significance value (2-tailed) of 0.000 (p <2 0.05) which means H1 is accepted so that there is a significant influence between the influence of Officer Performance and Satisfaction of PSC 119 ambulance patients, there is an Influence between Service and Satisfaction of PSC 119 Ambulance Patients in North Tapanuli Regency with the results that (2-tailed) is 0.000 (p <0.05), the Influence of Access to Patient Satisfaction by PSC 119 Ambulance Nurses in North Tapanuli Regency with the results that all variables are strongly and positively correlated with patient satisfaction (Coeff. correlation> 0.6) The most dominant variable that influences Service to satisfaction is empathy with a value of p = 0.006. It is expected that the health service can improve facilities and training regularly to all officers in order to provide better services.